A giant M2L3 metallo-organic helicate based on phthalocyanines as a host for electroactive molecules. Issue 21 (23rd February 2018) - Fazio, Ettore; Haynes, Cally J. E.; de la Torre, Gema; Nitschke, Jonathan R.; Torres, Tomás
Abstract : An unprecedented phthalocyanine-based, metallo-organic helicate (Fe2 Pc3 ) has been assembled and proved as a host for large redox-active guests such as fullerenes and naphthalenediimides. Abstract : An unprecedented Fe2 Pc3 metallo-organic helicate has been assembled using a bidentate phthalocyanine (Pc) ligand, 2-formylpyridine and Fe(OTf)2 . This giant helicate has proved itself as a host for large redox-active guests such as fullerene and naphthalenediimide derivatives. Photoactivated electronic interactions between components occur in the host–guest complex.